Implementation of Fuzzy Logic in NPCs for Online Multiplayer Games Using Photon - Muhammad Haris; Mursyidah Mursyidah; Atthariq Atthariq (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2025)
This thesis discusses the implementation of fuzzy logic techniques in managing the behavior of non-playable characters (NPC) in a game with online multiplayer features that utilize the Photon platform. Games with online multiplayer modes have become very popular, but managing NPC behavior in a multiplayer context is often a complex challenge, requiring high adaptability to changes in the environment and player behavior. This research describes the process of implementing fuzzy logic on NPCs to improve interactivity and player experience. in multiplayer online games. There are three main components in this study: the NPC behavior model, the selection of relevant environmental variables, and the design of fuzzy rules for decision making. In addition, this thesis also describes the integration of Photon technology as a multiplayer platform, which allows players to interact in real-time in the game.The experimental and evaluation results show that the use of fuzzy logic in managing NPC behavior in multiplayer online games can increase the level of realism in player interactions with NPC characters. This makes a positive contribution to the player's gaming experience and results in a more challenging and exciting gameplay in an online multiplayer context. This research provides valuable insights into the use of fuzzy logic in online multiplayer games as well as the integration of Photon as an effective multiplayer platform.